Dyrygent - lider zespołu rozrywkowego w muzycznym ruchu amatorskim = Conductor - leader of music band in the amateur music movement - Piotrowski, Ryszard J. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article is trying to define what is potential, predispositions, and qualities of a modern conductor. A conductor is also, in fact, a leader, educator and instructor in a conducted ensemble, operating in the community within the amateur art movement. Every good band leader faces certain challenges.
Keywords: artistic activities; conductor; educator; ensamble; group synergy; leader; music education; music instructor; performance group; teamwork